2017
DOI: 10.4208/aamm.2016.m1530
|View full text |Cite
|
Sign up to set email alerts
|

Rock Stress Around Noncircular Tunnel: a New Simple Mathematical Method

Abstract: A new simple mathematical method has been proposed to predict rock stress around a noncircular tunnel and the method is calibrated and validated with a numerical model. It can be found that the tunnel shapes and polar angles affect the applicable zone of the theoretical model significantly and the applicable zone of a rectangular tunnel was obtained using this method. The method can be used to predict the values of the concentrated stress, and to analyze the change rate of rock stress and back to calculate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…The applicability of the criterion to other roadways, whose instability is mainly attributed to the retreat of longwall panels, needs further investigation. This is because longwall-affected roadways may experience different failure mechanism, [43][44][45][46][47] comparing to the roadway failure caused by high in situ stress condition.…”
Section: Discussionmentioning
confidence: 99%
“…The applicability of the criterion to other roadways, whose instability is mainly attributed to the retreat of longwall panels, needs further investigation. This is because longwall-affected roadways may experience different failure mechanism, [43][44][45][46][47] comparing to the roadway failure caused by high in situ stress condition.…”
Section: Discussionmentioning
confidence: 99%
“…In 2017, Shen et al [16] investigated a new simple mathematical method to predict rock stress around a noncircular tunnel, and the method is calibrated and validated with a numerical model. It can be found that the tunnel shapes and polar angles affect the applicable zone of the theoretical model significantly, and the applicable zone of a rectangular tunnel was obtained using this method.…”
Section: Introductionmentioning
confidence: 99%
“…Optimizing the design of such a cylinder requires an understanding of the elastoplastic behavior of the material [4]. Many numerical and analytical works have been done on this subject, especially on uniform rotating discs, to predict the stress field, deformations, and rupture, to avoid the risk of damage when the device is subjected to different loading conditions [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. In 2005, Ahmet N. Eraslan et al [4] obtained in the context of the small deformation theory analytical solutions on flat deformations in elastic tubes operably under pressure grades.…”
Section: Introductionmentioning
confidence: 99%
“…Power-law grading is used for material gradation pattern. In 2017, Wenlong Shen et al [11] investigated a new simple mathematical method to predict rock stress around a noncircular tunnel and the method is calibrated and validated with a numerical model. It can be found that the tunnel shapes and polar angles affect the applicable zone of the theoretical model signiïňĄcantly and the applicable zone of a rectangular tunnel was obtained using this method.…”
Section: Introductionmentioning
confidence: 99%